Impact of side branch calcification on bifurcation percutaneous coronary intervention: Analysis from the PROGRESS-BIFURCATION registry - Uluganyan M. (My University, 2025)
Background:The impact of side branch (SB) calcification on the outcomes of bifurcation percutaneous coronary intervention (PCI) remains understudied.Methods:We examined the impact of SB calcification assessed by coronary angiography on procedural characteristics and outcomes of 1,866 bifurcation PCIs (1,646 patients) performed at five centers between 2014-2025 from the PROGRESS-BIFURCATION registry (NCT05100992).Results:Moderate or severe SB calcification was present in 420 patients (25.5%). Patients with moderate or severe SB calcification were older and had more comorbidities including hypertension, dyslipidemia, history of heart failure, prior myocardial infarction, PCI and coronary artery bypass graft surgery. Moderate or severe SB calcification lesions were more complex with higher left main (LM), left anterior descending, left circumflex and right coronary artery stenoses, higher V-RESOLVE scores (16 vs 13, p<0.001), higher rates of ostial lesions (18.6% vs 6.0%, p<0.001), moderate or severe main vessel calcification (95% vs 19%, p<0.001) and longer side branch lesion length (10 vs 5 mm, p<0.001). In patients with vs without moderate or severe SB calcification the main vessel was more likely to be the LM (46.2% vs 17.6%, p <0.001) and two-stent techniques were more likely to be used (42.3% vs 25.0%, p<0.001) while provisional stenting use was lower (51.7% vs 70.5%, p<0.001). Technical success was similar (93.5% vs 95.1%, p=0.182) and procedural success was lower (88.3% vs 92.7%, p=0.005) in patients with moderate or severe SB calcification driven by higher major adverse cardiovascular events (MACE) (5.5% vs 2.7%, p=0.007). Moderate or severe SB calcification was associated with longer fluoroscopy (28 vs 18 min, p<0.001) and procedure times (114 vs 67 min, p<0.001), higher air kerma radiation dose (1.65 vs 1.30 Gy, p<0.001), and higher in-hospital mortality (2.1% vs 0.7%, p=0.026). During a median follow-up of 1,037 days moderate or severe SBC was independently associated with higher MACE (adjusted hazard ratio [HR]: 1.49, 95% confidence interval [CI]: 1.14, 1.95, p=0.004), driven by higher mortality (HR: 2.63, CI: 1.96, 3.53, p<0.001), target vessel revascularization (HR: 1.73, CI: 1.23, 2.42, p=0.001) and MI (HR:1.53, CI: 0.99, 2.36, p=0.036)Conclusions:Bifurcation PCI in patients with moderate or severe SB calcification was associated with higher complexity and worse in-hospital and follow-up outcomes.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Kalp ve Kalp Damar Sistemleri; Tıp Genel & Dahili; Clinical Medicine (Med); Clinical Medicine; Cardiac & Cardiovascular Systems; Medicine General & Internal; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Kardiyoloji ve Kardiyovasküler Tıp; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Cardiology and Cardiovascular Medicine; Medicine (miscellaneous); General Medicine